2010
DOI: 10.1128/jcm.00522-10
|View full text |Cite
|
Sign up to set email alerts
|

PCR-Based Pooling of Dried Blood Spots for Detection of Malaria Parasites: Optimization and Application to a Cohort of Ugandan Children

Abstract: Sensitive, high-throughput methods to detect malaria parasites in low-transmission settings are needed. PCR-based pooling strategies may offer a solution. We first used laboratory-prepared samples to compare 2 DNA extraction and 4 PCR detection methods across a range of pool sizes and parasite densities. Pooled Chelex extraction of DNA, followed by nested PCR of cytochrome b, was the optimal strategy, allowing reliable detection of a single low-parasitemic sample (100 parasites/l) in pool sizes up to 50. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
91
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 32 publications
8
91
0
Order By: Relevance
“…The result of this study indicated that the nested PCR protocol A was more efficacy and superior for detection of P. falciparum over protocol B. The detection limit of this protocol was good and similar as found in previous nested PCR studies [5,[23][24][25].…”
Section: Discussionsupporting
confidence: 63%
“…The result of this study indicated that the nested PCR protocol A was more efficacy and superior for detection of P. falciparum over protocol B. The detection limit of this protocol was good and similar as found in previous nested PCR studies [5,[23][24][25].…”
Section: Discussionsupporting
confidence: 63%
“…10 A likely explanation is that some DNA is lost during binding and elution in the spin column. A caveat to this finding is that we only evaluated three PCR assays; assays more sensitive to inhibitors may benefit from use of highly purified DNA obtained from the spin-column technique.…”
Section: Discussionmentioning
confidence: 99%
“…Extracted DNA was stored at −20 C until use. Nested PCR for cytochrome B mitochondrial DNA using 5 μL template DNA followed previously published methods, 10 except that for round one of amplification primers were CB1ab (5 -TTTAGCAAGTCGATATACACCAGA-3 ) and CB2ab (5 -CTTTAACTTGCCAACTCCCTATCA-3 ); and temperature cycling conditions were: 5 minutes at 94 C, 40 cycles at 94 C for 30 seconds, 62.5 C for 90 seconds, 68 C for 90 seconds, and a final elongation at 68 C for 10 minutes, yielding an amplicon length of 1241 base pairs. Single round PCR of microsatellites was performed for two previously published loci (TA40 and PfG377) using 1 μL of template DNA in a 5 μL reaction volume.…”
Section: Methodsmentioning
confidence: 99%
“…Pooling samples before analysis facilitates the large-scale application of this technique for surveillance by reducing cost and analysis time. 7,8 As Thailand aims for malaria elimination, including elimination of artemisininresistant parasites, improvements in case detection are necessary. We aimed to determine if pooled real-time PCR could be integrated with the existing active case detection systems in Thailand and if so, if it would be more effective than microscopy for identifying low-density parasitemias.…”
mentioning
confidence: 99%